ChemInform Abstract: Sonochemical Procedures; the Main Synthetic Method for Synthesis of Coinage Metal Ion Supramolecular Polymer Nano Structures. Issue 47 (3rd November 2016) - Shahangi Shirazi, Fatemeh; Akhbari, Kamran
Abstract: Review: 72 refs.